Pengaruh Kualitas Produk dan Promosi Media Online Garasi Besi dengan Pintu Kayu terhadap Minat Beli Pelanggan “Pintu Garasi Kens” - Darmawan, Muhammad Wisnu; Lailla, Nor (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The purpose of this study is to determine the effect of product quality and online media promotion on customer purchase intention, either partially or simultaneously. This quantitative-descriptive study uses probability sampling technique, with a sample of 300 respondents who are customers of the “Kens Garage Door” business. Data analysis uses SPSS program. The results of the study state that there is a significant effect of product quality on purchase intention; there is a significant effect of online media promotion on purchase intention; and, there is a simultaneous effect of product quality and online media promotion on customer purchase intention. Thus, this study shows that product quality and online media promotion have an important influence on the strategy of creating purchase intention in consumers.